Modeling energy requirements for oxygen production on the Moon - Dorian Leger; Fardin Ghaffari-Tabrizi; Matthew Shaw; Joshua Rasera; David Dickson; Baptiste Valentin; Anton Morlock; Freja Thoresen; Aidan Cowley (Proceedings of the National Academy of Sciences, 2025)
Spacecraft using combustion engines require substantial amounts of oxygen for their propellant. The Moon could be a source of oxygen for rocket propellant, since the material composing the lunar surface can be processed to extract oxygen. However, little is known about overall energy requirements of the processes described in the literature for oxygen extraction from lunar regolith. This knowledge gap constrains the planning of lunar missions, since the scale of energy infrastructure required for oxygen production facilities is not well characterized. This study presents an energy consumption model for oxygen production via hydrogen reduction of the mineral ilmenite (FeTiO 3 ). We consider an end-to-end production chain starting from dry regolith as the feedstock. The production includes the following process steps: excavation, transportation, beneficiation, hydrogen reduction, water electrolysis, liquefaction, and zero boil-off storage. The model predicts the energy demand per kilogram oxygen produced based on adjustable parameters for each process step. As expected, the model indicates a strong dependence on feedstock composition. For regolith composed of 10 wt% ilmenite, the model predicts that a total of 24.3 (± 5.8) kWh is needed per kg of liquid oxygen produced. This study confirms that the hydrogen reduction and electrolysis steps have the highest energy requirements in the production chain. Sensitivity analysis reveals that the enrichment factor of the beneficiation process is the most critical parameter for optimizing energy utilization. Overall, this study provides a parameterized end-to-end model of energy consumption that can serve as a foundation for various production systems on the Moon.